Assessment of the self-care activities among hypertensive patients working in an industrial setting: A cross-sectional study - Manisha Gogurla; Darivemula Surendra Babu; Sudha Bala; Devidas P Tondare; Susheela Islavath; Vinolya Ganduri (Journal of Family Medicine and Primary Care)
Background: According to the fifth National Family Health Survey, an estimated 21.3% of women and 24% of men aged 15 years and older in India were found to have hypertension. The Joint National Committee recommends that people with hypertension engage in six self-care activities. They are adhering to antihypertensive medication, maintaining or losing weight, following a low-salt diet, limiting alcohol, engaging in regular physical activity, and eliminating tobacco use. The objectives of the study are to assess the self-care activities in hypertensive patients among industrial workers and to determine the factors affecting the self-care activities. Materials and Methods: A cross-sectional study was conducted in a field practice area of the Department of Community Medicine, Hyderabad, and included 170 insured persons who worked in an industrial setting and had known hypertension. Data was collected using a standard questionnaire (H-SCALE AND PHQ-4). A binary logistics regression was done to determine the factors associated with self-care practices. Results: Medication adherence was 63.5%, adherence to a low-salt diet and physical activity was 23.5% and 32.4%, respectively. About 78.2% were nonsmokers and 57.1% abstained from alcohol. Good weight management practices were seen only in 10% of participants. The overall prevalence of poor self-care practices was found to be 51.8%. Factors like age, illiteracy, semi-skilled and skilled workers, participants perceived health status, and unsatisfactory working environment were significantly associated with poor self-care practices. Conclusion: Target health education for older adults and low-literacy groups on low-salt diets, exercise, and weight control. Enhance workplace health for industrial workers.